An Enhanced Fe–28Mn–9Al–0.8C Lightweight Steel by Coprecipitation of Nanoscale Cu‐Rich and κ‐Carbide Particles. Issue 7 (11th March 2020) - Yang, Lei; Li, Zhiming; Li, Xiang; Zhang, Yunhu; Han, Ke; Song, Changjiang; Zhai, Qijie
Abstract : Fe–Mn–Al–C austenitic matrix lightweight steels show a high ultimate tensile strength and total elongation but a relatively low yield strength. The yield strength is increased by coprecipitation of nanoscale Cu‐rich and κ‐carbide particles. For lightweight steel, strips of Fe–28Mn–9Al–0.8C (wt%) are prepared in near‐rapid solidification conditions, the addition of Cu up to 5 wt% leads to the coprecipitation of nanoscale Cu‐rich and κ‐carbide particles in certain heat‐treating conditions. The formation of Cu‐rich particles has promoted the precipitation of nanosized κ‐carbide particles. The yield strength of particle‐strengthened Fe–28Mn–9Al–0.8C–5Cu (wt%) austenitic matrix steel reaches 808 MPa with total elongation greater than 20%. Thus, the addition of 5 wt% Cu increases the yield strength of heat‐treated austenitic matrix lightweight steel without seriously deteriorating its plasticity by coprecipitation of nanoscale Cu‐rich and κ‐carbide particles. Abstract : Coprecipitation of nano‐scale Cu‐rich and κ‐carbide particles can be achieved in Fe–28wt%Mn–9wt%Al–0.8wt%C–5wt% Cu prepared under near‐rapid solidification and heat‐treating at 500 °C for 20 h, and formation of Cu‐rich particles may promote the precipitation of κ‐carbide particles during the heat‐treating. Therefore, the increase of yield strength can reach about 289 MPa in Fe–28wt%Mn–9wt%Al–0.8wt%C–5wt% Cu strip.